DOI: 10.14793/soc_etd.28
|View full text |Cite
|
Sign up to set email alerts
|

Work support, work-family enrichment, work demand and work well-being among Chinese employees : a study of mediating and moderating processes

Abstract: Work and family are the central and salient domains in one's life. Juggling work and family life has become a challenge for many employees and families (Hammer et al., 2005). This study proposed a theoretical model in which work to family enrichment functioned as the mediator between work support (support from supervisor, co-workers and organization) and work well-being (job satisfaction and psychological health), and also examined whether work demand buffered the impact of work support on work well-being. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 150 publications
(264 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Indian attitudes toward work and family have changed dramatically in the past few decades, especially with regard to gender roles (Warner and Hausdorf, 2009). Globalization, technological advancement and entry of large numbers of women into the workforce have helped to normalize the principle that men and women should hold equivalent roles and share work and household responsibilities equally (Tang, 2010). These shifts in social attitudes have raised interest in investigating how Indians manage their work and family domains and how their experiences of work domain improve the quality of their family life.…”
Section: Wfe In Indiamentioning
confidence: 99%
“…Moreover, Indian attitudes toward work and family have changed dramatically in the past few decades, especially with regard to gender roles (Warner and Hausdorf, 2009). Globalization, technological advancement and entry of large numbers of women into the workforce have helped to normalize the principle that men and women should hold equivalent roles and share work and household responsibilities equally (Tang, 2010). These shifts in social attitudes have raised interest in investigating how Indians manage their work and family domains and how their experiences of work domain improve the quality of their family life.…”
Section: Wfe In Indiamentioning
confidence: 99%
“…Work-family enrichment is thus a process intrinsic to work that generates positive results associated not only with family (Greenhaus & Powell, 2006), but also with work itself (McNall et al, 2010). Therefore, it can be seen as a work resource, as it facilitates the achievement of work goals (Bakker & Demerouti, 2014) and consequently leads employees to repay their organization with positive attitudes (McNall et al, 2010), as is the case of occupational satisfaction (Tang, 2010). In this sense, the meta-analysis conducted by McNall et al (2010) concluded that workfamily enrichment was positively associated with occupational satisfaction.…”
mentioning
confidence: 99%